2004
DOI: 10.1017/s0022029904000044
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic safety-margins do not differ between cows of high and low genetic merit for milk production

Abstract: Three galactopoietic stimuli, frequent milking (4X), bovine somatotrophin (bST) and thyroxine (T4) were used in an additive stair-step design to achieve maximum output (metabolic capacity) in six peak-lactation cows of high genetic merit (HT) and six of low genetic merit (LT). A further six of each merit were untreated controls (HC, LC). Milk yield was increased significantly by 4X, increased further by the combination of 4X and bST and increased further still and significantly by the full combination of 4X, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…Further maternal over-nutrition has been demonstrated to result in offspring metabolic programming (2,3) , in multiple organ systems, for example, pancreas and liver (2) , as well as in central and peripheral nervous systems involved in energy homoeostasis (4)(5)(6)(7) . Human epidemiological (2,8) and experimental animal studies (9)(10)(11)(12) have shown a correlation between maternal diet and milk composition. Few studies address the mechanisms by which maternal obesity induced by a high-fat diet regulates liver and mammary gland (MG) differentiation and function during lactation and the implications for the observed changes in milk synthesis and composition (13) .…”
mentioning
confidence: 99%
“…Further maternal over-nutrition has been demonstrated to result in offspring metabolic programming (2,3) , in multiple organ systems, for example, pancreas and liver (2) , as well as in central and peripheral nervous systems involved in energy homoeostasis (4)(5)(6)(7) . Human epidemiological (2,8) and experimental animal studies (9)(10)(11)(12) have shown a correlation between maternal diet and milk composition. Few studies address the mechanisms by which maternal obesity induced by a high-fat diet regulates liver and mammary gland (MG) differentiation and function during lactation and the implications for the observed changes in milk synthesis and composition (13) .…”
mentioning
confidence: 99%
“…Accordingly, the reduction in circulating thyroid hormones in early lactating dairy cows has been viewed as an energy sparing mechanism (Vernon et al 2002). This view is supported by increased energy expenditure and excessive weight loss in cows treated with exogenous thyroid hormones (Thomas 1953, Knight et al 2004. The hLeptin infusion partially corrected the thyroid hormone deficit and exacerbated the loss of body weight without impacting milk production, suggesting an increase in a nonmammary component of energy expenditure.…”
Section: Discussionmentioning
confidence: 68%
“…Plasma glucose and NEFA concentrations were not affected (P N 0.10) by genetic group. Lower plasma glucose and higher NEFA concentrations would have been expected in cows with higher genetic capacity due to their lower energy balance (Veerkamp et al, 2003) but responses have varied (Westwood et al, 2000;Åkerlind et al, 1999b;Knight et al, 2004). Westwood et al (2000) found reduced plasma glucose but similar NEFA concentrations in high merit cows, and explained the similar NEFA by a higher utilization for milk fat synthesis.…”
Section: Blood Metabolites and Hormonesmentioning
confidence: 86%
“…In late lactation, a numerical, but not significantly, higher (P = 0.18) IGF-1 concentration was observed in H cows than in L cows. In the studies of Michel et al (1991) and Åkerlind et al (1999b), IGF-1 was not affected by genetic merit, but higher IGF-1 concentrations in high genetic merit cows have been reported (Snijders et al, 2001;Knight et al, 2004).…”
Section: Blood Metabolites and Hormonesmentioning
confidence: 90%